Volatile and semi‐volatile organic compounds of respiratory health relevance in French dwellings. (15th June 2015) - Dallongeville, A.; Costet, N.; Zmirou‐Navier, D.; Le Bot, B.; Chevrier, C.; Deguen, S.; Annesi‐Maesano, I.; Blanchard, O.
Abstract: Over the last decades, the prevalence of childhood respiratory conditions has dramatically increased worldwide. Considering the time spent in enclosed spaces, indoor air pollutants are of major interest to explain part of this increase. This study aimed to measure the concentrations of pollutants known or suspected to affect respiratory health that are present in dwellings in order to assess children's exposure. Measurements were taken in 150 homes with at least one child, in Brittany (western France), to assess the concentrations of 18 volatile organic compounds (among which four aldehydes and four trihalomethanes) and nine semi‐volatile organic compounds (seven phthalates and two synthetic musks). In addition to descriptive statistics, a principal component analysis (PCA) was used to investigate grouping of contaminants. Formaldehyde was highly present and above 30  μ g/m 3 in 40% of the homes. Diethyl phthalate, diisobutyl phthalate, and dimethylphthalate were quantified in all dwellings, as well as Galaxolide and Tonalide. For each chemical family, the groups appearing in the PCA could be interpreted in term of sources. The high prevalence and the levels of these compounds, with known or suspected respiratory toxicity, should question regulatory agencies to trigger prevention and mitigation actions.